THE SPECTRUM OF AROUSAL AND ATTENTION: CAPTURING DELIRIUM SUPERIMPOSED ON DEMENTIA - Davis, D. (Innov Aging, 2017)
Detecting delirium superimposed-on-dementia (DSD) is difficult because assessment relies on cognitive tests that may be abnormal in both conditions. We hypothesised that assessments focusing more on the arousal-attention spectrum, and less on general cognition, would provide better empirical data for DSD diagnosis. We recruited patients aged ≥70y from five hospitals across Europe (excluding aphasia; severe hearing impairment). Delirium was diagnosed by physicians according to DSM-5 criteria including information from nurses, carers, and review of medical records. Dementia was ascertained by the Informant Questionnaire of Cognitive Decline in the Elderly (cut-off ≥3.5). Arousal was measured using the Observational Scale of Level of Arousal (OSLA), which assesses eye movement, eye opening, eye contact, posture, movement, and communication. Attention was measured by participants signalling each time an “A” was heard when “S-A-V-E-A-H-A-A-R-T” was read out. The sample included 114 persons (mean age 82y (SD 7); 54% women). Dementia alone was present in 25% (n=28), delirium alone in 18% (n=21), DSD in 27% (n=31), neither in 30% (n=34). Arousal-attention were assessed in n=109 (96%). Using OSLA, 83% participants were correctly identified (sensitivity 85%, specificity 82%, AUROC 0.92). The attention task correctly classified 76% (sensitivity 90%, specificity 64%, AUROC 0.80). Combining scores correctly classified 91% (sensitivity 84%, specificity 92%, AUROC 0.94), remaining high in the subset with dementia (93% correctly classified, sensitivity 94%, specificity 92%, AUROC 0.98). This combined arousal-attention assessment to detect DSD was brief yet with high diagnostic accuracy even in dementia. Such an approach could have major clinical utility for diagnosing DSD.